PENGARUH PERBEDAAN VARIETAS DAN STARTER PADA SILASE TEBON JAGUNG TERHADAP KECERNAAN BAHAN KERING DAN KECERNAAN BAHAN ORGANIK SECARA IN VITRO - Irham Fadli; Farida Fathul; Rudy Sutrisna; Liman Liman (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study aimed to determine the dry matter digestibility (DMD) and organic matter digestibility (OMD) in forage corn silage with two varieties (BISI-18 and NK-212) given two types of starter (molasses and bran). This research was conducted in May—August 2019 at the Laboratory of Animal Nutrition and Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. In vitro analysis of dry matter digestibility and organic matter digestibility by Tilley and Terry (1963). The experimental design used was factorial 2x2 in a Completely Randomized Design (CRD), with 3 replications. The factors studied were (1) corn stover varieties which consisted of two varieties (BISI-18 and NK-212) and (2) starter which consisted of two types of starter (molasses and bran). The results of this study indicate that there was no interaction (P>0,05) between the use of varieties of corn forage and starter sugar cane the dry matter digestibility, and organic matter digestibility. Duncan furher test, the use of different corn forage varieties has a significant effect (P<0,05) on silage the the dry matter digestibility, and organic matter digestibility. The best DMD value is found in the BISI-18 variety (59.07%) and The best OMD value is found in the BISI-18 variety (58.20%). The use of different types of starter has no significant effect (P>0.05) on the determine the dry matter digestibility, and organic matter digestibility of silage. Keywords: Corn Forage, Digestion, Dry matter, Organic matter, Silage